Local Community’s Acceptance of Mangrove Forest as A Sustainable Tourism Product: A Preliminary Findings - Hamimah Talib; Nurnadhira Najwa Zaidon; Rosmalina Abdul Rashid; Chan, Jennifer Kim Lian (BIMP-EAGA Unit for Tourism Development (BE-UTD), 2021)
The study was conducted to examine the local community's acceptance towards mangrove forest as a sustainable tourism product in Kampung Rampayan Laut and Kampung Nanamun, Kota Belud, Sabah, Malaysia. In addition to the above, it is also to determine the level of knowledge of the local community on the importance of mangrove forests as well as to determine the level of willingness of the local community to participate in mangrove forest management. These two specific sites were selected due to the increasing tourist’s influx in the area for mangrove forest rivercruise and fireflies watching. Purposive sampling technique was used which involved distribution of questionnaires to 150 respondents from both Kampung Rampayan Laut and Kampung Nanamun, which is about 10% from the actual population size. Likert scale was used in the questionnaire form, ranging from one which represents strongly disagree to five which represents strongly agree for each item to measure respondents’ level of acceptance, knowledge, and willingness to participate in mangrove forest management. The study found that the level of local communities’ acceptance is high which supports the efforts to make mangrove forest as a sustainable tourism product. This study also found that local communities have the basic knowledge on the importance of mangrove forests to the ecosystems and are willing to be involved in mangrove management. This study has identified the community’s acceptance towards mangrove forest as a sustainable tourism product through their perception of benefits acquired through mangrove forest tourism which could be used as a baseline data for wetland resource management to ensure sustainability.